PKM: Transformation of Geography Learning through Unmanned Aerial Vehicles – A Creative Solution to Enhance the Quality of Digital Mapping at SMA Negeri 3 Takalar - Syarif, Erman; Fathahillah; Abd Malik (Yayasan Ahmar Cendekia Indonesia, 2025)
This Community Service Program (PKM) aims to transform geography learning through the utilization of Unmanned Aerial Vehicle (UAV) technology as a creative solution to enhance the quality of digital mapping at SMA Negeri 3 Takalar. The activities were carried out in several stages: needs analysis, technical training on UAV operation and mapping software, field practice mentoring, and evaluation of improvements in teachers’ and students’ competencies. The application of UAVs equipped with GPS and high-resolution cameras, combined with ArcGIS software, enabled mapping learning to become more interactive, contextual, and project-based. The evaluation results showed a significant increase in both teachers’ and students’ knowledge and skills in operating UAVs, processing spatial data, and producing digital thematic maps. The program also fostered greater student interest in learning and strengthened teachers’ capacity to integrate geospatial technology into the geography curriculum. This PKM recommends the continuation of training and curriculum development based on technology to support spatial literacy at the secondary school level.